2019
DOI: 10.1111/ecpo.12131
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous effect of oil discoveries on democracy

Abstract: This paper evaluates the existence of a resource curse on political regimes using the Synthetic Control Method. Focusing on 12 countries, we compare their democracy level with the weighted democracy level of countries that have not experienced oil shocks and have similar pre‐event characteristics. We find that the exogenous variation in oil endowment does not have the same effect on all countries. In most cases, the event has a negative effect in the long run, but countries with a pre‐existing high level of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Scholars have defined "good" institutions in various ways. Some studies largely equate "good" or "strong" with "democratic" and have found that ex ante democratic countries are less likely to experience the political resource curse (Amundsen 2014;Arezki and Gylfason 2013;Karl 1997;Masi and Ricciuti 2019;Prichard et al 2018;Wright and Czelusta 2007). Operationalizing strong pre-existing institutions as "democracy" is therefore conceptually clear and empirical evidence supports democracy's ability to "immunize" countries from the curse.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have defined "good" institutions in various ways. Some studies largely equate "good" or "strong" with "democratic" and have found that ex ante democratic countries are less likely to experience the political resource curse (Amundsen 2014;Arezki and Gylfason 2013;Karl 1997;Masi and Ricciuti 2019;Prichard et al 2018;Wright and Czelusta 2007). Operationalizing strong pre-existing institutions as "democracy" is therefore conceptually clear and empirical evidence supports democracy's ability to "immunize" countries from the curse.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But why do some countries seem to escape this curse while others do not? Scholars studying the resource curse in both its political and economic forms-the latter stipulates that natural resource wealth produces slower economic growth-broadly agree that avoiding the curse largely depends on the quality of pre-existing governance institutions and/or the establishment of effective resource management institutions in the present (Adams et al 2019;Amundsen 2014;Badeeb et al 2017;Khanna 2017;Masi and Ricciuti 2019;Mehlum et al 2006;Papyrakis 2017;Prichard et al 2018;Robinson et al 2006;Tornell and Lane 1999;Torvik 2009;van der Ploeg 2011). Specifically, Amundsen contends: "A country will be cursed when the discovery of oil or diamonds, for instance, is made before accountable and democratic state institutions are established and consolidated" (2014,171).…”
Section: Introductionmentioning
confidence: 99%
“…The literature has pointed out the role of institutions as a crucial determinant of whether a country suffers a resource curse or not (e.g., Bhattacharyya and Hodler 2010;Boschini et al 2007;Brunnschweiler 2008;Collier and Hoeffler 2009;Ebeke et al 2015;El Anshasy and Katsaiti 2013;Masi and Ricciuti 2019;Melhum et al 2006;Omgba 2015). 11 Two explanations have been put forward to understand the role of institutions: one emphasizes rent-seeking mechanisms (Melhum et al 2006;Tornell and Lane 1999;Torvik 2002) and the other patronage (Caselli and Cunningham 2009;Robinson et al 2006).…”
Section: Why Do Some Countries See a Developmental Resource Curse And Others Do Not?mentioning
confidence: 99%
“…A number of papers argue, and empirically demonstrate, that institutions can mitigate or even reverse the resource curse (e.g. Hodler 2010, 2014;Boschini et al 2007;Brunnschweiler 2008;Ebeke et al 2015;El Anshasy and Katsaiti 2013;Masi and Ricciuti 2019;Melhum et al 2006;Omgba 2015). 4 Two explanations have been put forward to understand the role of institutions: one emphasizes rent-seeking mechanisms (Melhum et al 2006;Tornell and Lane 1999;Torvik 2002), and the other patronage (Caselli and Cunningham 2009;Robinson et al 2006).…”
Section: Resource Rents Fiscal Capacity and Political Institutionsmentioning
confidence: 99%